Efektivitas Program E-Payment One Stop Service Dalam Menunjang Pemungutan Pajak Bumi Dan Bangunan di Kabupaten Karimun - Fitran Sah; Novi Winarti; Ardi Putra (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
The E-Payment one-stop service program is an electronic tax payment designed by the regional revenue agency to make it easier for the public to make land and building tax payments. However, this program faces various challenges, including a lack of public understanding of the existence and mechanism of using the E-Payment program in utilizing devices such as smartphones to access the E-Payment website or application, as well as network constraints that often cause system disruptions. The purpose of this study is to analyze the effectiveness of the E-Payment one-stop service program in supporting the PBB collection in Karimun Regency. By using Sutrisno's theory (2010) with indicators of program understanding, target accuracy, timeliness, goal achievement, and real improvement. The research method used is a qualitative approach with data collection through in-depth interviews and documentation. The results of the study show that, first, the E-Payment program by regional revenue agencies shows significant progress in modernizing public services, by involving the community and focusing on ease of access.